Morfoanatomi Polen Flora Mangrove Di Pantai Banjir Kanal Timur, Semarang - Titi Nurul Qodriyyah; Sri Widodo Agung Suedy; Sri Haryanti (Jurnal Akademika Biologi, 2015)
Indonesia has the largest mangrove area in the world that covering an area of 2.5-5 million ha. Indonesia's vast mangrove area has been declined by 50%. Locations that becoming sampling stations, namely East Flood Canal (BKT) undergo abrasion that caused water-logging in mangrove forest areas that affect the diversity of plants in it. Plant diversity can be learned through the pollen of plants. Morphology-anatomy can be used as additional criteria for identifying plant species. The aim of this study was to determine the diversity of plants and morphology-anatomy pollen of plants on the coast BKT. Sampling was conducted using roaming at both locations. Data were analyzed by making the description and classification. The results showed that mangrove forests in BKT have a diversity of plants as many as 9 species. Morphology-anatomy pollen of different species have a variety of shapes and sizes. Keywords: mangrove, morphology-anatomy, pollen, Semarang